Mind the gender gap in farmers’ preferences for weather-index insurance - Akter, Sonia; Krupnik, Timothy J.; Rossi, Frederick; Khanam, Fahmida; International Rice Research Institute; International Maize and Wheat Improvement Center (International Food Policy Research Institute, 2015)
The findings highlight the importance of investment in institutional credibility as a precondition to attract women farmers to sign up for WII, particularly in an investment environment characterized by poor governance and weak institutional accountability. In addition, the findings indicate the importance of continued investments to boost women’s agency and financial literacy, as a necessary precondition to enable WII schemes to work. Lastly, it is imperative that a WII scheme must be as realistic and simple as possible for the intended clients, particularly women, to understand the insurance product. Without these three key interventions, the study indicates that farmers’ interest in WII, particularly among women, is likely to remain low in Southern Bangladesh.